A new family of supramolecular multiferrocenyl rhomboids：Synthesis,characterization,and their electrochemical behavior - Ou-Yang, Jiang-Kun; Chen, Li-Jun; Xu, Lin; Wang, Cui-Hong; Yang, Hai-Bo (Chinese chemical letters, 2013)
Two novel,supramolecular,multiferrocenyl rhomboids 5 and 6 have been successfully constructed from newly designed 60 ferrocenyl donor precursor 1 via coordination-driven self-assembly.The structures of all multiferrocenyl rhomboids were characterized by multinuclear NMR（~1H and ~（31）P）,CSI-TOF-MS, and PM6 semi-empirical molecular simulation,and their electrochemical behaviors have been investigated.